Conception et réalisation d'un robot parallèle à trois degrés de liberté - حميد, طه ضياء الحق; بكوش, علاء الدين (University of El Oued جامة الوادي, 2018)
تركز هذه المذكرة على التصميم الأمثل للروبوت المتوازي بثلاث درجات من الحرية، ويتبعها تطبيق مع دراسة هندسية وحركية لهذا الأخير، وفي هذه الدراسة اخترنا الروبوت دلتا الخطي كنموذج لبناءه. للحصول على الأبعاد الهندسية للروبوت المتوازي، نقدم نمذجة الأبعاد والحركة للهيكل المختار، تظل هذه الخطوة مهمة جدًا نظرًا لأن معايير الأداء لبنية معينة تعتمد بشدة على أبعاد هذه البنية. تليها صياغة لمشكل التحسين مع الأخذ بعين الاعتبار الأداء الحركي كمعيار. وأخيرًا، نقدمThis memory focuses on the optimal design of a parallel robot with three degrees of freedom, followed by a realization with a geometric and kinematic study of this system. In this study, we choose the linear Delta robot as a parallel manipulator to realize. In order to obtain the geometrical parameters of a parallel kinematic machine, we present a dimensional and kinematic modeling of the chosen structure, this step remains a very important task since the performance criteria of a given architecture depend very strongly on the dimensions of the structure. Its geometric parameters. Followed by a formulation of an optimization problem taking into consideration the kinematic performances as performance criteria. Finally, we present the different steps of Delta robot construction, with 3D modeling realized using the SolidWorks software. المراحل المختلفة من بناء روبوت دلتا، مع تصميم نماذج ثلاثية الأبعاد باستخدام برنامج SolidWorks
مذكرة ماسترهندسة ميكانيكية تخصص إلكتروميكانيك
Keywords: Parallel Robot, Delta Robot, Geometric and Kinematic Model; روبوت المتوازي، دلتا روبوت، نموذج هندسي وحركي.